1982
DOI: 10.1111/j.1469-8137.1982.tb03394.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Rainforest Regeneration

Abstract: SUMMARYMeasurements in two sub-tropical rainforests demonstrated that (i) in one rainforest succession, total soil phenols varied dramatically throughout the study year with soils from the 'climax' rainforest exhibiting highest phenol levels, the nature of these phenolic compounds was not investigated; (ii) in the other rainforest succession, the 55-year-oid regrowth exhibited highest total phenols, but the level of condensed tannins increased throughout the succession. The highest level of nitrification was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…One early study of nitrogen cycling in a subtropical rainforest identified a pattern of more rapid rates of nitrification and nitrogen mineralization compared to temperate forests (Chandler and Goosem 1982). Later, Hiroto and Haibara (1994) used a laboratory incubation method to compare mineralization potentials at two slope positions in forest soils in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…One early study of nitrogen cycling in a subtropical rainforest identified a pattern of more rapid rates of nitrification and nitrogen mineralization compared to temperate forests (Chandler and Goosem 1982). Later, Hiroto and Haibara (1994) used a laboratory incubation method to compare mineralization potentials at two slope positions in forest soils in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of nutrients and phenolics typically differ in leaves of plants growing under different environmental conditions and in leaves of different ages, and these chemical traits may influence patterns of herbivory (Fox and Macauley, 1977;Chandler and Goosem, 1982;Coley, 1983a,b;Waterman et al, 1984;Meyer and Montgomery, 1987;Mole and Waterman, 1988;Denslow et al, 1990;Nichols-Orians and Schultz, 1990). Tannins are one class of phenolics that may influence selection of leaves by herbivores (Waltz, 1984;Mole and Waterman, 1988;Schultz, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Marquis, personal communication). This may be because these growth conditions result in elevated concentrations in some plant species of carbon-based secondary compounds like tannins (Chandler and Goosem, 1982;Nichols-Orians, 1991b). However, leaves of plants growing in the sun and in nutrient-rich soil often have higher concentrations of both condensed tannins and foliar nutrients than the leaves of plants growing in the forest understory (Field and Mooney, 1986;Denslow et al, 1990;Nichols-Orians, 1991a), and these sun leaves have been found to be more acceptable to leafcutter ants than understory leaves (Nichols-Orians, 1991a;R.…”
Section: Introductionmentioning
confidence: 99%
“…High NO 3 À -N /NH 4 + -N ratio in the present study indicated that our soils, like the subtropical rainforest of Australia, predominated in NO 3 À -N (Chandler and Goosem 1982). However, relatively greater accumulation of NO 3 À -N during the post-wet and dry seasons under all the tree species could probably be due to lack of leaching and run off losses owing to low amount of rainfall, and low vegetative uptake.…”
Section: Discussionmentioning
confidence: 42%